Development of a prototype to access biodegradability of TPU shoe soles under controlled conditions - Fernandes, I.P. (2017)
In the last years, the increasing problems posed by waste management have stimulated the interest in developing more sustainable and bio-based solutions for the footwear industry, including the use of biodegradable materials. As part of the NEWALK project, the objective of this work consisted in optimizing and implementing a respirometry system prototype. Besides evaluating different variables, two different approaches for measuring the evolved CO2 were assayed. Compared to manual titration, the use of conductivity offers the advantage of an automatic continuous monitoring.